1987
DOI: 10.14430/arctic1753
|View full text |Cite
|
Sign up to set email alerts
|

Summer Distribution of Bowhead Whales, <i>Balaena mysticetus</i>, Relative to Oil Industry Activities in the Canadian Beaufort Sea, 1980-84

Abstract: Aerial surveys in 1980-84 showed that summer distribution of bowheads in the Beaufort Sea varied markedly between years. Distribution varied both outside and within the "main industrial area" (MIA), the area of island construction, drilling and intensive ship and helicopter traffic. Numbers of bowheads in the MIA were high in 1980, lower in 1981, near zero in 1982 and very low in 1983-84. The few whales in the MIA in 1983-84 were mainly near its edges, contrary to 1980-8 1. These data, plus limited evidence fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 12 publications
(19 reference statements)
1
32
0
Order By: Relevance
“…Feeding has been observed in the Canadian Beaufort Sea in summer and in both the Alaskan Beaufort Sea and near the Russian coast of the Chukchi Sea during autumn. Over the past 3 decades, offshore oil exploration and (more recently) development have occurred in some parts of the summer and autumn range in the Canadian and Alaskan Beaufort Sea (Richardson et al 1987). The feeding habitats of the whales during the summer and the fall migration are generally known, but the relative amounts of food consumed from various parts of the seasonal range are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding has been observed in the Canadian Beaufort Sea in summer and in both the Alaskan Beaufort Sea and near the Russian coast of the Chukchi Sea during autumn. Over the past 3 decades, offshore oil exploration and (more recently) development have occurred in some parts of the summer and autumn range in the Canadian and Alaskan Beaufort Sea (Richardson et al 1987). The feeding habitats of the whales during the summer and the fall migration are generally known, but the relative amounts of food consumed from various parts of the seasonal range are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The bowhead spring migration follows fractures in the sea ice around the coast of Alaska, generally in the shear zone between the shorefast ice and the mobile pack ice. During the summer, most of the population is in relatively ice-free waters in the southern Beaufort Sea, an area often exposed to industrial activity related to petroleum exploration and extraction (e.g., Richardson et al 1987, Davies 1997. During the autumn migration, bowheads select shelf waters in all but "heavy ice" conditions, when they select slope habitat (Moore 2000).…”
Section: Habitat Concernsmentioning
confidence: 99%
“…The use of whale calls for censusing (Clark and Ellison, 1989), the potential role of calls in bowhead ice navigation (Ellison et al, 1987), and observations of whales breaking ice and feeding (George et al, 1989;Carroll et al, 1987) during the migration have been reported in association with the spring census. Summer and fall studies have focused on determining whale distribution and behavior in relation to oil and gas activities in Canadian and Alaskan Beaufort Sea OCS waters (e.g., Richardson et al, 1987;Moore et al, 1989b). These studies described bowhead feeding areas (Richardson, 1987;Ljungblad et al, 1986a), migratory routes and timing (Moore et al, 1988;Moore et al, 1989a), and behavioral responses to offshore industrial activities, including man-made underwater noise (Richardson et al, 1986;Ljungblad et al, 1988;Miles et al, 1987;Davis, 1987), but did not address estimates of bowhead numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Summer and fall studies have focused on determining whale distribution and behavior in relation to oil and gas activities in Canadian and Alaskan Beaufort Sea OCS waters (e.g., Richardson et al, 1987;Moore et al, 1989b). These studies described bowhead feeding areas (Richardson, 1987;Ljungblad et al, 1986a), migratory routes and timing (Moore et al, 1988;Moore et al, 1989a), and behavioral responses to offshore industrial activities, including man-made underwater noise (Richardson et al, 1986;Ljungblad et al, 1988;Miles et al, 1987;Davis, 1987), but did not address estimates of bowhead numbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation